La planificación en la cooperación descentralizada española. El caso de las Comunidades Autónomas - Illán Sailer, José Carlos (Revista Española de Desarrollo y Cooperación, 2023)
Over the last ten years the Regional and Local Aid Cooperation in Spain has undertaken a major effort in constructing an institutional and strategic framework to operate accordingly. Besides the amount of ODA given by the Regional and Local Authorities, there is also a tendency to adopt the strategic planning as the main instrument to promote an active role in the Spanish Aid System. The article focuses on the causes that led to such decition and the main obstacles and challenges faced by the Regional policy-makers.